The mitochondrial protein frataxin is essential for heme biosynthesis in plants - Maliandi, María Victoria (2010)
Frataxin, a conserved mitochondrial protein implicated in cellular iron homeostasis, has been involved as the iron chaperone that delivers iron for the Fe–S cluster and heme biosynthesis. However, its role in iron metabolism remains unclear, especially in photosynthetic organisms. In previous work, we found that frataxin deficiency in Arabidopsis results in decreased activity of the mitochondrial Fe–S proteins aconitase and succinate dehydrogenase, despite the increased expression of the respective genes, indicating an important role for Arabidopsis thaliana frataxin homolog (AtFH). In this work, we explore the hypothesis that AtFH can participate in heme formation in plants. For this purpose, we used two Arabidopsis lines, atfh-1 and as-AtFH, with deficiency in the expression of AtFH. Both lines present alteration in several transcripts from the heme biosynthetic route with a decrease in total heme content and a deficiency in catalase activity that was rescued with the addition of exogenous hemin. Our data substantiate the hypothesis that AtFH, apart from its role in protecting bioavailable iron within mitochondria and the biogenesis of Fe–S groups, also plays a role in the biosynthesis of heme groups in plants.